2022
DOI: 10.1080/19490976.2022.2094664
|View full text |Cite
|
Sign up to set email alerts
|

Improved gut microbiome recovery following drug therapy is linked to abundance and replication of probiotic strains

Abstract: Probiotics have been used for decades to alleviate the negative side-effects of oral antibiotics, but our mechanistic understanding on how they work is so far incomplete. Here, we performed a metagenomic analysis of the fecal microbiota in participants who underwent a 14-d Helicobacter pylori eradication therapy with or without consumption of a multi-strain probiotic intervention ( L. paracasei CNCM I-1518, L. paracasei CNCM I-3689, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Finally, the relative abundance of Bifidobacterium was lower in subjects with recent antibiotic intake (Mann-Whitney, P < 0.001) [Supplementary Figure 2]. Despite the considerable analytical differences between studies, this dataset reproduced the major associations previously reported between Bifidobacterium and age [27] , lifestyle [28] , health status [1,29,30] , and antibiotic use [31][32][33] in individual cohorts.…”
Section: Analysis Of Pooled Metagenomic Studies Recapitulates Major F...supporting
confidence: 61%
See 2 more Smart Citations
“…Finally, the relative abundance of Bifidobacterium was lower in subjects with recent antibiotic intake (Mann-Whitney, P < 0.001) [Supplementary Figure 2]. Despite the considerable analytical differences between studies, this dataset reproduced the major associations previously reported between Bifidobacterium and age [27] , lifestyle [28] , health status [1,29,30] , and antibiotic use [31][32][33] in individual cohorts.…”
Section: Analysis Of Pooled Metagenomic Studies Recapitulates Major F...supporting
confidence: 61%
“…Here, we studied the variability of the gut microbiome as a function of the resident Bifidobacterium community, using a public database compiling curated metagenomics-based studies, mostly performed in adults from Western countries. We first checked that we could reproduce the previously reported findings of a lower abundance of Bifidobacterium species in antibiotic users [31][32][33] and individuals with diseases [1] or adopting a nonwesternized lifestyle [28] , the differential prevalence of most Bifidobacterium species depending on age [10] , the high prevalence of B. longum throughout the human lifespan [27] , and the higher prevalence of B. adolescentis in healthy subjects than in those with diseases [29,30] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, previous studies showed significant improvements in the gut ecology of patients who received probiotic interventions at the end of antibiotic therapy compared to patients who did not receive interventions. 30 Probiotic intervention in the first hours after antibiotic intake can provide good prevention of pCDI, as demonstrated in several clinical…”
Section: Antibiotics Precede Probioticsmentioning
confidence: 95%
“…Probiotics, even as milk-fermented products, have been used empirically for decades to alleviate the negative side effects of oral antibiotics, but understanding of the way they work is so far incomplete. A metagenomic analysis of the fecal microbiota of 135 subjects, who received a 14 d scheme of antibiotics revealed a rapid alteration of gut microbiota, a decrease in richness and diversity, a bloom of pathobionts of the family Enterobacteriaceae , and the depletion of several taxa including Bifidobacterium and butyrate producers [ 54 ]. The co-administration of probiotics showed a small, but measurable, benefit on microbiome recovery after antibiotics, which was linked to the detection and replication of specific probiotic strains.…”
Section: To Prevent Antibiotic-associated Diarrheamentioning
confidence: 99%